Åtta invandrares syn på vilka faktorer som har bidragit till deras känsla av välbefinnande - Enetoft,Sara; Karlsson,Ingrid (2006)
The subject of this study is factors that contribute to immigrants wellbeing in their new country. Our purpose was to describe and examine different factors that according to eight immigrants have contributed to their wellbeing in Sweden. Our main question was: Which factors have, according to our respondents, contributed to their wellbeing in Sweden. To achieve this, we have conducted qualitative interviews with eight different individuals. We also collected current documents and research related to the subject matter. We chose three different theoretical perspectives: Antonovsky´s Sense of coherence, Maslow´s Hierarchy of needs and Mischel´s CAPS-theory (cognitive-affective personality system) as models for the explanation of our analysis. The result of our survey was that we could detach six different categories which the respondents expressed had contributed to their wellbeing. These were: Family and friends, social safety nets, cultural understanding, dreams and goals, satisfactory occupation and the significance of the individuals own efforts.
Keywords: välbefinnande; invandrare; salutogent perspektiv; Social changes, theory of social work; Sociala förändringar, teorier om socialt arbete